Weight changes and serum sodium concentrations after an ultradistance multisport triathlon - Speedy, D. B.; Campbell, R.; Mulligan, G.; Robinson, D. J.; Walker, C.; Gallagher, P.; Arts, J. H. (Clinical Journal of Sport Medicine, 1997)
OBJECTIVE: This study describes the incidence of hyponatremia and the weight changes during an ultradistance multisport triathlon. DESIGN: Descriptive research. SETTING: A 1-day triathlon in which each athlete kayaks 67 km, cycles 148 km, and runs 23.8 km. PARTICIPANTS: Forty-eight athletes competing in the race were studied. INTERVENTIONS: None. MAIN OUTCOME MEASURES: All subjects were weighed before the race and on completion of the race. A blood sample for serum sodium was taken at the finish of the race. RESULTS: The mean weight change over the course of the race was a loss of 2.5 kg (SD +/- 1.7, n = 48), or a mean percentage loss of body weight of 3.1% (SD +/- 2.07). This was highly statistically significant (p < 0.0001) using the Student paired t test. No athletes gained weight, and six athletes maintained their same weight. Only one athlete was hyponatremic (Na = 134 mEq/L). This athlete maintained his weight over the course of the race and he did not seek medical attention. The mean serum sodium concentration at the end of the race was 139.3 mEq/L (SD = 2.28, n = 47). There was a significant correlation (r = 0.30, p = 0.04) between sodium levels and weight change during the race: the greater the weight loss, the higher the serum sodium concentration. There was no significant correlation between the degree of weight loss and athletes' finishing times (r = 0.11, p = 0.45). CONCLUSIONS: Symptomatic hyponatremia did not occur in the 1996 Coast to Coast multisport triathlon, although one athlete had borderline hyponatremia. Athletes lose significant amounts of weight over the course of this multisport event, but nevertheless manage to complete the race.